Convergence between the dimensional PD models of ICD-11 and DSM-5: a meta-analytic approach - Hualparuca-Olivera, Luis; Caycho-Rodríguez, Tomás; Torales, Julio; Ramos-Campos, Dayana (Frontiers in Psychiatry, 2023)
In the current diagnostic systems, the International Classification of Diseases-11th rev. (ICD-11) and the Diagnostic and Statistical Manual of Mental Disorders-5th ed. (DSM-5), the evaluation and diagnosis of personality disorder (PD) aim at dimensional examination of the severity of its dysfunction and the stylistic features that accompany it. Since their implementation, or even before, several measures have been developed to assess PD severity and traits in both models. Thus, convergent validity metrics have been reported with various PD measures; however, the convergence of the same constructs included in the measures of these two models remains undefined. The objective of the present review was to examine whether there is a sufficient relationship between PD measures of the ICD-11 and DSM-5 AMPD in the general population. For this meta-analytic review, systematic searches were conducted in Web of Science, PubMed, Scopus, and Google Scholar. We included studies that reported Pearson’s r correlations without restrictions on language, age, sex, setting, type of sample, or informant of the measures. We excluded associations with anankastia, psychoticism or the borderline pattern because they were not comparable between one dimensional model and the other. We examined the quality of the evidence with the JBI Critical Appraisal Checklist for Analytical Cross Sectional Studies, and performed the random effects meta-analysis with the ‘meta’ package of the RStudio software. Of the 5,629 results returned by the search, 16 studies were eligible; and showed moderate quality. The risk of bias was manifested by not specifying the details of the sample, the recruitment environment, and the identification and control of confounding factors. Thirteen studies provided two or more correlations resulting in a total of 54 studies for meta-analysis. The overall effect size estimate (correlation) was moderate for the overall model (r = 0.62, 95% CI [0.57, 0.67], p < 0.0001, I2 = 97.6%). For the subgroup of associations, ICD-11 severity model and DSM-5 AMPD severity model, the correlation was also moderate (k = 10, r = 0.57, 95% CI [0.48; 0.66]; I2 = 92.9%); as for the subgroup of associations, ICD-11 traits model and DSM-5 AMPD traits model (k = 44, r = 0.63, 95% CI [0.57; 0.69], I2 = 97.9%). The convergent validity between measures of PD severity and traits between one diagnostic system and another has been demonstrated in this review and they can probably be used interchangeably because they also measure the same constructs. Future research can address the limitations of this study and review the evidence for the discriminant validity of these measures.